Florística e estrutura de um fragmento de Floresta Ombrófila Montana na Serra do Valentim, Iúna, Espírito Santo - Zorzanelli, João Paulo Fernandes (2012)
The objectives of this study were to list the species a stretch montane rain forest Serra do Valentim, verify the geographical distribution of the same and analyze the structure and floristic similarity. F ertile botanical materials were collected from trees, shrubs, herbs, epiphytes, vines and lianas along tracks and trails on 25 field trips between the years 2011 and 2012. A total of 391 species, 220 genera and 99 families were registered. Among these, 27 were considered endangered, three endemic to the state of Espírito Santo, and three possible new to science. The most geographical pattern found was neotropical, although many species (about 10%) were restricted to Atlantic Forest vegetation in southeastern Brazil. The vegetation structure was analyzed in a total of 10 transects of dimensions 50 x 2 meters, and recorded all individuals (living and dead), among trees, shrubs and lianas with DBH = 2.5 cm. Diameter was measured for all individuals and the overall height was estimated only for individuals alive. The floristic similarity was estimated using the Bray-Curtis index and WPGMA algorithm was used to group the vegetation related to 12 floristic listings. Were found 146 species, 95 genera and 53 families, and the species with the highest importance value was Euterpe edulis Mart. The Shanon index (H '= 3.60 nats / ind.) was close to that found for the unspoilt forests of the Atlantic Forest and the Pielou index (J = 0.72) was considered high. The similarity values were low revealing lacking consistency in cluster analysis. The results showed the large gap in terms of floristic knowledge to the vegetation of the state of Espírito Santo, as well as the area surrounding the Caparaó, suggesting a process of intensification of collections and floristic and structural studies, due to the great wealth found. The distinction of the vegetation from Serra do Valentim in relation the others analyzed represents the heterogeneity along the Atlantic in response to several factors, among physiographic, edaphic, climatic and altimetric. These factors contribute to the formation of punctual centers of diversity restricted to small regions. Given the wealth found, threatened flora, level of endemism and possible new species, Serra do Valentim is worthy of conservation policies.